2013
DOI: 10.1007/s00334-013-0421-3
|View full text |Cite
|
Sign up to set email alerts
|

Stable carbon isotope analysis as a crop management indicator at Arslantepe (Malatya, Turkey) during the Late Chalcolithic and Early Bronze Age

Abstract: In Near Eastern archaeology, studies on crop management during the early stages of civilisation have been based on cuneiform texts and only recently have geoarchaeological surveys and archaeobotanical studies tried to identify agricultural practices. Nevertheless, direct evidence for irrigation and water management is very rare and difficult to interpret. New possibilities for analysing these ways of management have been provided by stable carbon isotope analysis of ancient crops. In this study carbon isotope … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…environmental changes from East to West Mediterranean (Marvelli et al 2013;Peñ a-Chocarro et al 2013;Kouli 2014;Masi et al 2014;Sabato et al 2014;Sadori et al 2013Sadori et al , 2014b. Our newly published data (this issue) and data collected in past years by several colleagues and ourselves indicate that there is a clear need to find the right way to integrate palaeoecological and neoecological data.…”
Section: Collaboration Provides New Insightsmentioning
confidence: 57%
See 1 more Smart Citation
“…environmental changes from East to West Mediterranean (Marvelli et al 2013;Peñ a-Chocarro et al 2013;Kouli 2014;Masi et al 2014;Sabato et al 2014;Sadori et al 2013Sadori et al , 2014b. Our newly published data (this issue) and data collected in past years by several colleagues and ourselves indicate that there is a clear need to find the right way to integrate palaeoecological and neoecological data.…”
Section: Collaboration Provides New Insightsmentioning
confidence: 57%
“…Moreover, soil chemistry change and physical transformation are induced by ploughing, hydrography changes and land reclamation Bosi et al 2014a); the use of fire changes the biomass equilibrium (Bal et al 2011;Sadori et al 2014c); breeding or pastoral activities induce a selection of species towards development of shrubby associations or loss of vegetation (Florenzano & Mercuri 2012) especially under increasing drought (Garcea et al 2013). Consequently, there is the spreading of complex agricultural management (Marvelli et al 2013;Peñ a-Chocarro et al 2013;Masi et al 2014) that archaeobotany has revealed to have been highly advanced in Bronze age (Mercuri et al 2014a and Roman times (Bowes et al 2014); voluntary dispersion of new plants imported for food or decoration (Sadori et al 2009;Rosati et al 2014), and socio-political decisions affecting landscape management (Mensing et al 2013).…”
Section: Collaboration Provides New Insightsmentioning
confidence: 98%
“…In addition, wood remains have also provided data on structural elements, fuel, tools, and movable objects (Alvaro, 2010;Piccione et al, 2015;Sadori and Masi, 2012;Sadori et al, 2006Sadori et al, , 2008Vignola et al, 2014). Moreover, the archaeobotanical assemblage constituted an excellent database for paleoenvironmental reconstruction based on stable carbon isotope analysis (Baneschi et al, 2012;Masi et al, 2013aMasi et al, , 2013bMasi et al, , 2014. These studies indicate a wetter climate between the end of the fourth and the entire third millennium BC compared to today.…”
Section: Paleo-land Cover and Environmental Settingmentioning
confidence: 97%
“…During the EBA IA, the Arslantepe communities were mainly pastoral. As highlighted by stable isotope analysis on crop remains, people adapted crop management to climate and organizational change in terms of both cereal species selection and the distribution of fields as opposed to pasturelands (Masi et al, 2014). Finally, after 3800 cal.…”
Section: Yearmentioning
confidence: 99%
“…Stable isotope analysis is becoming increasingly widespread in archaeobotanical research as a powerful method for investigating agricultural practices and land use patterns (Aguilera et al 2008;Bogaard et al 2013;Fraser et al 2013;Heaton et al 2009;Kanstrup et al 2014;Masi et al 2014;Vaiglova et al 2014). Plant stable carbon (δ 13 C) and nitrogen (δ 15 N) isotope ratios vary in relation to a range of environmental factors (Dawson et al 2002) including agricultural practices, and these variations can be analysed in archaeobotanical remains (Fiorentino et al 2015;Szpak 2014).…”
Section: Introductionmentioning
confidence: 99%